Overcoming constraints to animal traction through a collaborative research network - Goe, M.R. (International Livestock Centre for Africa, 1990)
Briefly reviews the status of animal traction in sub-Saharan Africa, giving estimates of the numbers and types of draft animals in different countries. Mentions the objectives of the animal traction thrust of ILCA and discusses the benefits of developing an animal traction network.